Evaluation of Antibacterial Activity of Cymbopogon citratus Ethanolic Leaf Crude Extract against Streptococcus pneumoniae isolated from Kampala International University Teaching Hospital Western Campus, Uganda - Ntulume, Ibrahim; Victoria, Ninsiima; Adam, Abubakar Sunusi; Aliero, Adamu Almustapha (International Journal of Applied Sciences and Biotechnology, 2019)
Streptococcus pneumoniae is the common cause of pneumonia, meningitis, bacteremia and Septicemia among adults and children worldwide. Resistance to antimicrobials agents has been reported among S. pneumoniae which necessitate the need for alternative intervention such as ethno-medicinal plants. Cymbopogon citratus is an ethno-medicinal plant which is known to have pharmacological activities including antibacterial activity. This study aimed at determining the in vitro antibacterial activity of C. citratus ethanolic leaves crude extract against clinical isolates of S. pneumoniae. A fresh leaves of C. citratus were collected early in the morning; shed dried, pulverized and extracted using ethanol (96%) using standard extraction method. The antibacterial activity, Minimum Inhibitory and Minimum Bactericidal Concentrations of C. citratus ethanolic leaves crude extract were determined against clinical isolates of S. pneumoniae. C. citratus ethanolic leaves extract crude showed antibacterial activity against S. pneumoniae at 500mg/ml concentration with mean and standard deviation zone of inhibition (26.33 ± 1.53 mm) in comparison with that of 250mg/ml concentration which gave 20.33 ± 2.08 mm mean and standard zone of inhibition. The minimum inhibitory concentration of the plant crude extract against S. pneumoniae was 15.63 mg/ml while the minimum bactericidal concentration was 125mg/ml. The study found that C. citratus leaves ethanolic crude extract was active against S. pneumoniae. It is recommended that studies should be done focusing on isolation of specific phytochemicals of the C. citratus leaves crude extract and then determines their antibacterial activity against clinical isolates of S. pneumoniae. Int. J. Appl. Sci. Biotechnol. Vol 7(1): 31-38